Beban Kerja Perawat terhadap Implementasi Patient safety di Ruang Rawat Inap - Retnaningsih, Dwi; Fatmawati, Diah Fatmawati (Jurusan Keperawatan FIKES UNSOED, 2016)
One of the goals of patient safety systems is a declining unexpected events which are results of multiple problems included humane resources, inadequate policies and procedures to decline in events that could occur due to several problems and one of them is the problem of human resources, policies and procedures even technical failures of factors that risk for causing infection. Ã‚Â One of them is high nurseÃ¢â‚¬â„¢s workload due to insufficient staffs or nurses. Ã‚Â The purpose of this study was to examine the relationship between the nurseÃ¢â‚¬â„¢s workload and the implementation of patient safety in the inpatient units at Tugurejo Public Hospital Semarang. A cross sectional study invited 155 nurses to participate. The total sampling technique was applied. Chi Square test tested the hypothesis. The result showed that the nurseÃ¢â‚¬â„¢s workload tended to high level (58.7%), while mostly the implementation of patient safety was unfavorable (60.6%). Chi-Square test reported X2=6.807 (p= 0.0009). There is a significant relationship between the nurseÃ¢â‚¬â„¢s workload and the implementation of patient safety in the hospital inpatient Tugurejo Semarang.